Catfight - Pivec, Nataša (Družboslovne razprave, 2013)
The article discusses "catfight" as an umbrella term and pejorative word for any kind of intra-women aggression (relational or physical). The author derives the definition of the phenomenon from challenging a cultural assumption about women and cats (also present in the naming of this act), both constituted as Other, the construction of normative femininity as complicit to hegemonic masculinity, and the gender ambiguity or non-binary of the phenomenon (a catfight as a queer act). An analysis of selected media representations showed that the catfight is positioned as liminal and at the intersection of gender, sexuality and class.
Keywords: Gender studies; Študije spolov; Ženskost; Femininity; Družbena konstrukcija; Social construction; Mass media; Množični mediji; woman; ženske